Soap Tree (Kelreiteria Paniculata) In the Conditions of Namangan Multiplication (Eurasian Research Bulletin, 2022)
Soap tree - this Asia and America in the tropics growing sapinda of the family leafy small trees or bushes. Soap of the tree fruits, soap nuts, diameter about 1, 5 see which was fruits as they are suddenly up to 3 seeds own into takes Soapy berries when ripe, their surface soft and velvet case will be. When cooked, it hardens, nut shell like, therefore for name – “soap nuts”. Dry soap nuts have a dark brown or black color depending on the type of drying.